Competence of Islamic Religious Education Teachers in Information Technology-Based Learning to Increase Learning Interest of Vocational High School Students - Agustina Agustina; Ahmad Nurdiansyah; Hadi Widayat (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2023)
This study focuses on the competence of Islamic Religious Education (PAI)teachers in using information technology-based learning to enhancestudents' learning interest at SMK Ganesa Sekampung, East Lampung. Theresearch questions address the teachers' proficiency in using informationtechnology media, the types of media employed in PAI learning, as well asthe challenges faced and solutions implemented by teachers in integratinginformation technology into the learning process. The purpose of this studyis to examine the PAI teachers' skills in using information technologymedia, to identify the media utilized, and to explore the problems andsolution efforts encountered during technology-based learning at SMKGanesa Sekampung. This research adopts a qualitative approach withdescriptive analysis methods. Data were collected through interviews,questionnaires, and document analysis. The findings reveal that thecompetence of PAI teachers in using information technology mediaremains low. This is primarily due to the teachers' limited familiarity withusing technology in their daily routines. The media used includepresentation slides, videos, and other digital tools. A major issue faced isthe lack of training opportunities in information technology, whichcontributes to the teachers' limited skills. As a solution, teachers participatein training sessions and are supported by the school through the provisionof facilities such as computers and projectors.